2021
DOI: 10.3390/ma14061356
|View full text |Cite
|
Sign up to set email alerts
|

Cooling System with PCM Storage for an Office Building: Experimental Investigation Aided by a Model of the Office Thermal Dynamics

Abstract: The application of energy storage filled with phase-change material (PCM) is recently increasingly considered in active cooling systems. Such a design offers a higher density of thermal energy accumulation when compared with water storage. However, the optimum use of PCM storage is possible when its dynamic characteristics during the loading and unloading process are well recognized. Due to the complexity of the interaction between all elements of the heating/cooling system, a theoretical estimation of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this study three commercial PCMs, RT15, RT18 HC, and RT22 HC, were investigated. These PCMs can be used to support heating or cooling systems in buildings and have low phase transition temperatures that fall within the range of 10 °C to 23 °C [ 20 , 21 , 22 , 23 , 24 ]. PCM samples of volume amounting to 10 mL were applied to glass tubes with a diameter of 16 mm and a length of 160 mm (except tube No.…”
Section: Methodsmentioning
confidence: 99%
“…In this study three commercial PCMs, RT15, RT18 HC, and RT22 HC, were investigated. These PCMs can be used to support heating or cooling systems in buildings and have low phase transition temperatures that fall within the range of 10 °C to 23 °C [ 20 , 21 , 22 , 23 , 24 ]. PCM samples of volume amounting to 10 mL were applied to glass tubes with a diameter of 16 mm and a length of 160 mm (except tube No.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed simplified numerical model of the office building describes heat transfer and accumulation between the indoor air and the wall, as well as the heat transfer to or from the surroundings. The model presented is similar to the one presented in [37,55]. Based on Eq.…”
Section: Office Buildingmentioning
confidence: 99%
“…Due to the complexity of the interaction between all elements of the heating/cooling system, a theoretical estimation of the LHTS profits is hard to perform in a reliable way. In order to solve this problem, the application of energy storage filled with PCM was experimentally investigated by Karwacki [37]. A case study of an actual adsorption cooling plant with different fin shapes in the LHTS showed that the optimum fin configuration can save up to 46% of the heat storage cost as compared to LHTES without fins.…”
Section: Introductionmentioning
confidence: 99%
“…Storage of heat or cold can be done with thermal energy storage (TES) using phase change materials (PCMs). PCMs incorporated in latent heat energy storages (LHTES) are used to store heat from solar collectors [ 3 , 4 ], to store energy from household wind power plants [ 5 ], in building heating and cooling systems [ 6 , 7 ], to support heat pumps and waste heat recovery installations [ 8 ], to support district heating networks [ 9 , 10 ]. In addition, PCMs are used to cool photovoltaic panels [ 11 ] and are also used in building structural elements like walls [ 12 , 13 , 14 ], windows [ 15 ] and roofs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%